Effects of remifentanil on the recovery quality among pediatric candidates for dental procedures under general anesthesia - Nosrat Nourbakhsh; Nasser Kaviani; Reza Salari-Moghaddam; Shirin Marzoughi (Wolters Kluwer Medknow Publications, 2022)
Background: Remifentanil is a short-acting synthetic opioid, seems to facilitate hospital discharge, induce less agitation and better recovery quality. The aim of this study was to investigate the effects of remifentanil on the quality of recovery among healthy children who were candidate for dental procedures under general anesthesia. Materials and Methods: This study was a double blind randomized controlled clinical trial on healthy children who referred to the Department of Pediatric dentistry, School of Dentistry, Isfahan University of Medical Sciences. Both groups were anaesthetized using 5 mg/kg thiopental sodium, 1 μg/kg fentanyl and 0.6 μg/kg atracurium. The first group received propofol to maintain anesthesia and the second group was given remifentanil along with propofol. Then, the time span to regain consciousness, level of agitation during recovery and time of discharge were monitored and compared between the two groups. Data were analyzed using the Mann-Whitney U-test, and the Kruskal-Wallis test at P < 0.05 level of significance. Results: Findings showed that the propofol + remifentanil group recovered faster than the propofol group. Chi-square test showed a significant difference in recovery time between the two groups (P < 0.05). About 45 min after regaining consciousness, the mean pediatric anesthesia emergence delirium score in the propofol group was 4.02 ± 2.19 and was significantly higher than the propofol + remifentanil group (3.02 ± 2.83) (P < 0.05). In addition, the mean Postanesthetic Discharge Scoring System score in the propofol group was 6.04 ± 1.74 and was significantly higher than the propofol + remifentanil group (7.58 ± 2.14) (P < 0.05). Conclusion: Combination of propofol and remifentanil significantly reduced the time taken for recovery, discharge and agitation level compared to propofol.